Comparative ontogeny of the digestive tract of Oncorhynchus mykiss ♀ x Salmo trutta caspius ♂ triploid hybrids to their parental species. (30th November 2020) - Najafpour, Babak; Dorafshan, Salar; Paykan Heyrati, Fatemeh; Canario, Adelino V. M.; Power, Deborah M.
Abstract: The ontogeny of the gastrointestinal tract of the hybrid between female rainbow trout, RT ( Oncorhynchus mykiss ) and male Caspian brown trout, CBT ( Salmo trutta caspius ) was compared to the parental species. Larvae were collected for histology and enzymatic assays (amylase, lipase and trypsin) at 3, 6, 9, 12, 15, 18, 21, 26, 31, 35, 40 and 45 days post‐hatch (dph). The development of the gastrointestinal tract (GI‐tract) and the onset of digestive enzyme production was variable between groups. The GI‐tract post‐hatch was a relatively simple tubular structure, and a rudimentary oesophagus was differentiated from other regions at 3 dph in all studied groups. The pyloric caeca and the U‐shaped stomach were clearly visible at 26, 35 and 40 dph in RT, triploid hybrid and CBT, respectively. An abrupt increase in trypsin activity at 31, 35 and 45 dph was identified in CBT, RT and the triploid hybrid, respectively. The increasing activity of trypsin and decreasing activity of lipase during larval development suggests that the CBT, RT and triploid hybrid rely more on dietary proteins than lipids with increasing age. The hybrid grew better and had a faster GI‐tract development than CBT, while RT performed best overall.